(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Micro, Small and Medium Enterprises (MSMEs) play an important role in supporting the rural economy. However, many MSMEs in rural areas still face the obstacle of low product sales value due to the suboptimal implementation of branding. This Community Service Learning (CSL) activity aims to develop the branding of MSME products in Batumarta 2 Village, Ogan Komering Ulu (OKU) Regency, particularly in Air Jati Hamlet, as an effort to increase the selling value of local products. The methods used in this community service programme included observation, interviews, mentoring, and direct implementation with MSME actors. The main programme involved creating brand names and product logos that were applied to packaging label designs. The results of the programme showed that the implementation of branding was able to build a clearer and more attractive product identity, increase consumer appeal, and potentially increase the selling value of local MSME products.